The role of melatonin in preventing radiation-induced intestinal injury - Sezen, Orhan; Erdemci, Burak; Calik, Muhammet; Koc, Mehmet (Imprimatur Publications, 2021)
Purpose: Despite the therapeutic effects of radiotherapy on tumor cells, it has potential severe adverse effects on the sur- rounding normal tissues. Acute or chronic intestinal adverse effects that are likely to occur in patients undergoing radio- therapy for pelvic and abdominal cancers lead to increased morbidity, significant impairment of the quality of life, and economic losses. Various biological, chemical and pharma- cological agents are being tested to protect from and to treat radiation enteritis. This experimental study aimed to inves- tigate the protective effects of melatonin against radiation induced intestinal injury when administered before radiation exposure in rats. Methods: In the present study, villus height and the number of villi in the ileum and jejunum of rats receiving two dif- ferent doses of intraperitoneal melatonin (5 and 10 mg/kg) prior to a single fraction of radiation given at a dose of 8 Gy to the abdominal region, was evaluated by histopathological examination 3 and 7 days after radiation exposure. Results: At a dose of 5 mg/kg, melatonin was found to be effective in preventing radiation-induced injury to villus height in the jejunum and the number of villi in the ileum and jejunum, and at a dose of 10 mg/kg it was also effective in preventing radiation-induced injury to villus height in the ileum. Conclusions: Melatonin is effective for the prevention of radiation-induced intestinal injury. This outcome can be considered an evidence to test melatonin in clinical trials.
Keywords: intestinal injury; melatonin; radiation enteritis; radioprotective; radiotherapy